LEVEL OF EDUCATION, LENGTH OF SERVICE, AND WORKLOAD OF NURSES ON THE COMPLETENESS OF NURSING CARE DOCUMENTATION - Fitriana Kartikasari; Muhammad Purnomo; Ifa Nailatul Izaa; Putri Novi Kristiani ((IJP) Indonesia Jurnal Perawat, 2024)
Documentation is a basic element in accountability for the performance of the nursing profession. Recording nursing care documentation is an obligation that must be carried out by nurses. The obligation to record nursing care documentation is stated in the Decree of the Minister of Health of the Republic of Indonesia regarding licensing and implementation of nursing practice which states that nurses are required to carry out nursing records systematically. To determine the relationship between the level of education, length of work and workload of nurses with the completeness of nursing care documentation at the Sunan Kudus Islamic Hospital. This research is a correlational analytical research with an analytical survey method. An analytical survey itself is a survey or research that tries to explore how and why health phenomena occur. p-value chi-square test obtained from the analysis of education level and workload with completeness of professional secretary documentation was 0.000 (p0.05), then the results of analysis of length of work with completeness of civil servant documentation was 0.027 (p0.05 ) which means there is a significant relationship between level of education, length of work, and workload and the completeness of nursing care documentation. There is a relationship between the level of education, length of work, and workload of nurses and the completeness of nursing care documentation at Sunan Kudus Islamic Hospital.